Thromboelastography in ruptured abdominal aortic aneurysm management: lessons from vascular, cardiac, and trauma surgery - Gniedziejko, Michał; Halman, Joanna; Kimilu, Nina; Folwarski, Marcin; Siemiński, Mariusz (Frontiers in Cardiovascular Medicine, 2025)
Ruptured abdominal aortic aneurysm (rAAA) is a critical surgical emergency. Thromboelastography (TEG) is a viscoelastic, point-of-care test that provides a comprehensive real-time assessment of coagulation and fibrinolysis. Although TEG has been successfully adopted in trauma and cardiac surgery for individualised transfusion guidance, its role in rAAA has not been sufficiently explored. We conducted a review of studies published between 2009 and 2024 to assess the utility of TEG or rotational thromboelastometry (ROTEM) in rAAA management. Evidence from vascular surgery suggests reduced blood-product transfusions and postoperative bleeding. Additional data from cardiac surgery and emergency/trauma demonstrated improved survival, fewer reoperations and cost efficiency. Although there are few direct studies on the utility of TEG in rAAA and these are mostly descriptive, the results presented in this review suggest its potential role in vascular emergencies. To confirm this, well-designed prospective studies are essential to determine when and how TEG should guide decision-making in this critical setting.